Everybody wants some!! - Linklater, Richard, 1960-; Deutch, Zoey, 1994-; Amelio, Austin; Hoechlin, Tyler, 1987- (Hollywood, California : Paramount, 2016)
A group of college baseball players navigate through their new-found freedoms and responsibilities of college life.
Originally released as a motion picture in 2016.
Dolby digital 5.1, wide screen 1.85:1.
Cinematography, Shane F. Kelly ; production designer, Bruce Curtis ; editor, Sandra Adair.
Zoey Deutch, Austin Amelio, Tyler Hoechlin, Blake Jenner, Ryan Guzman.
MPAA rating: R.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Keywords: Baseball players -- Drama; College students -- Drama; Nineteen eighties -- Drama; Fiction films; Feature films; Comedy films